2018
DOI: 10.1163/15685411-00003125
|View full text |Cite
|
Sign up to set email alerts
|

Description of Xiphinema hangzhouense sp. n. (Nematoda: Longidoridae) from the rhizosphere of Magnolia grandiflora in Hangzhou, Zhejiang Province, China

Abstract: Xiphinema hangzhouensesp. n. is described from the rhizosphere ofMagnolia grandiflorain Hangzhou, China. The new species is characterised by having a monodelphic reproductive system, slim body, total stylet = 186-192μm long and vulva located anteriorly at 27.6-31.2% of total body length. The new species has a gonad 400-450μm long with a simple uterus and no Z-organ. The female tail is elongated conoid with a rounded terminus. The species has four juvenile stages and no male was found. The polytomous identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Our phylogenetic studies suggested that species in the morphospecies group 1 are not monophyletic, and morphospecies grouping was only established for the convenience of identification and do not always reflect the evolutionary history, which is consistent with other studies (Handoo et al, 2016;Cai et al, 2018). Considering the high variability in the morphological characters in Xiphinema species, it is necessary to use integrated morphological and molecular approaches in species diagnosis, especially in making a regulatory decision regarding the movement of soil and plant material.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our phylogenetic studies suggested that species in the morphospecies group 1 are not monophyletic, and morphospecies grouping was only established for the convenience of identification and do not always reflect the evolutionary history, which is consistent with other studies (Handoo et al, 2016;Cai et al, 2018). Considering the high variability in the morphological characters in Xiphinema species, it is necessary to use integrated morphological and molecular approaches in species diagnosis, especially in making a regulatory decision regarding the movement of soil and plant material.…”
Section: Discussionsupporting
confidence: 84%
“…This morphospecies group comprises species with anterior genital branch completely absent to a very small post uterine sac. Among 12 species in this group, i.e., X. brasiliense, X. chambersi, X. ensiculiferum, X. fagesi, X. hunaniense, X. hangzhouense, X. monasiae, X. monohysterum, X. naturale, X. orthotenum, X. radicicola and X. winotoi (Loof and Luc, 1993;Loof et al, 1996;Cai et al, 2018), only a few species were described with molecular characterizations. This study added another species with complete morphological and molecular characterization, which will help to enhance the knowledge and understanding to the classification of this group of nematodes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations